International experience of ethnic repatration: comparative analysis (on the example of Kazakhstan, Kyrgyzstan and China) (Journal of Philosophy Culture and Political Science, 2018)
The article analyzes the international experience of ethnic migration (on the example of Kazakhstan, Kyrgyzstan and China), deals with the issue of return, resettlement, adaptation, integration of returning ethnic groups to their historical homeland. The choice of cases is based on the «Most Similar System Design» (MSSD), developed by John Stuart Mill, and is thus aimed at selecting cases that are comparable, but have led to different results. Comparative analysis of repatriation programs is mainly based on the study of official documents (constitutions, laws, amendments, texts of official state programs and statements of heads of state), materials on social adaptation and social integration of returnees (results of sociological research). Key words: repatriation, migration, comparative analysis, repatriates immigrants, compatriots, oralmans, kayrilman, returnees, diaspora